Analisis Efektivitas “Customer Delight Program” Terhadap Motivasi Kerja Karyawan Di Shangri-La Hotel Surabaya - Rocky Hermansyah; Eddy M. Sutanto (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2012)
This research was taken place at Shangri-La Hotel Surabaya, an international management hotel. The population of research were 600 respondents. The purpose of this research was to understand the effectiveness of Customer Delight Program and employees’ work motivation of Shangri-La Hotel Surabaya. The analysis technique used quantitative analysis. The result of research showed that there was a relationship between Customer Delight Program and employees’ work motivation Shangri-La Hotel Surabaya.